TWO MESOZOIC OCEANIC PHASES RECORDED IN THE BASIC AND METABASIC ROCKS OF THE NAIN AND ASHIN-ZAVAR OPHIOLITIC MÉLANGES (ISFAHAN PROVINCE, CENTRAL IRAN - Shirdashtzadeh, Nargess; Torabi, Ghodrat; Arai, Shoji (Ofioliti, 2011)
The Mesozoic ophiolitic mélanges of Nain and Ashin-Zavar are located in the western part of the Central-East Iranian microcontinent (CEIM), along the major faults of Nain-Baft and Dorouneh. They contain two different groups of highly metamorphosed rocks (amphibolitic rocks, schists, marbles and quartzites) formed through metamorphism of oceanic basaltic and sedimentary units, and also some less metamorphosed rocks (sheeted dikes, pillow lavas, limestones and radiolarian cherts), that were tectonically melanged. These features show that they formed in two distinct phases. Geochemical data point to an island arc tholeiitic affinity for the amphibolitic rocks, and to a MORB nature for the pillow lavas and sheeted dikes that are related to a back-arc basin. Accordingly, oceanic crust extensional processes should have been active during two phases: a- In Early Jurassic, the Nain and Ashin-Zavar oceanic crust segments started spreading and producing diabasic dikes and pillow lavas, covered by pelagic sediments, then they suffered a high-grade metamorphism during the closure of this oceanic sector around the Middle Jurassic. b- During Early-Late Cretaceous to Paleocene, oceanic spreading produced sheeted dikes, massive basalts, and basaltic pillow lavas thoroughout the Austrian orogenic phase. There is no evidence of high-grade metamorphism as amphibolitic rocks. Radiolarian cherts and Globotruncana limestones of Late Cretaceous age cover the basaltic rocks.